Books as Sacred Beings. Issue 1 (24th June 2019) - Watts, James
Abstract : Research on the ritualization of sacred texts highlights the common cross-cultural analogy between books and people or other beings. In this essay, I argue that this analogy stems from a reader's experience of using books and the effects that books seem to exert on readers. Three different effects can arise from ordinary book use: an out-of-body experience, an experience of transcendence through the resurrection of ideas, and a transformative encounter that encourages religious description as a theophany. These three effects correspond to the ritualization of books in the semantic, expressive, and iconic dimensions. This correspondence raises questions about the influence of literacy on religious experience. It also opens the possibility that ordinary book use may provide a new avenue for analyzing religious experience.